Legal Gaps in Waste Management Regulation of Indonesia’s Fashion Industry - Ghufroni, Achmad; Silaswaty, Femmy; Yudanto, Dika (Jurnal Ilmu Hukum Kyadiren, 2025)
The fashion industry is among the sectors with significant potential to cause environmental pollution, particularly through liquid waste discharge, carbon emissions, and microplastic contamination. Despite these risks, Indonesia’s existing legal framework remains general in nature and lacks specific provisions addressing the environmental impacts of the fashion sector. This study aims to analyze both national and international legal frameworks concerning the environmental health implications of the fashion industry, identify normative and implemented weaknesses in current regulations, and assess the potential for harmonization with international legal principles and sustainability approaches, such as Extended Producer Responsibility (EPR). Employing normative juridical methods and a comparative legal approach, the study finds that Indonesia’s national regulations have yet to effectively address the distinct characteristics and environmental risks associated with the fashion industry. The study concludes by underscoring the urgent need for the development of responsive sector-specific regulations, the reinforcement of supervisory and enforcement mechanisms, and the integration of international principles to promote an environmentally sustainable fashion industry.